Предмет: Алгебра,
автор: ke1tas
Разложить на множители x^3-y^3+3y^2-3y+1=
Ответы
Автор ответа:
0
x³ - y³ + 3y² - 3y + 1 = x³ - (y³ - 3y² + 3y - 1) = x³ - (y - 1)³ =
= (x - (y - 1) )(x² + x(y - 1) + (y - 1)² ) = (x - y + 1)(x² + xy - x + y² - 2y + 1)
= (x - (y - 1) )(x² + x(y - 1) + (y - 1)² ) = (x - y + 1)(x² + xy - x + y² - 2y + 1)
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: nastyade
Предмет: История,
автор: dayuprime7857504
Предмет: География,
автор: belosnejka01
Предмет: Физика,
автор: МАХD